The Relationship between the Level of Adherence to Antiretroviral Drugs (ARVs) Use to Viral Load Levels in Outpatient HIV Patients - Yulyana, Zahara; Andriani, Medi; Dewi, Rasmala (Jurnal Multidisiplin Indonesia, 2025)
Human Immunodeficiency Virus (HIV) is a disease that is contagious to humans so that it can lower the immune system and be susceptible to diseases. Drugs given to treat HIV infection and improve the quality of life of People With HIV/AIDS (ODHA) are antiretrovirals (ARVs). Adherence to taking antiretrovirals is an important factor in the success of therapy and reducing the amount of HIV virus in the body of ODHA, so that a high level of adherence has a fairly good or undetectable viral load result. The purpose of this study is to find out if there is a relationship between compliance with viral load levels. The research method was conducted with a cross sectional design, starting from May to June 2024. The data used are the results of the MMAS-8 questionnaire that has been validated and filled out directly at the Putri Ayu Health Center in Jambi City and the results of the viral voad level laboratory. Sampling with consecutive sampling. The data obtained in the analysis by bivariate analysis used the Cramer's V with a degree of significance of p-value <0.05. The results in this study were obtained by 11 (52.4%) respondents with a high level of compliance so that the results of viral load were not detected, there were 10 respondents with a moderate and low level of compliance so that 8 (38.1%) respondents had a detected viral load result and 2 respondents were not detected. There was a significant relationship with adherence to taking antiretroviral drugs to viral load levels with a result of 0.000 p-value <0.05 or 5%.